2019
DOI: 10.1080/21691401.2018.1549062
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Flot2 targeted by miR-449 acts as a prognostic biomarker in glioma

Abstract: Flotillin-2 (FLOT2) was reported as oncogene and involves in the pathogenic process of several cancers, yet the precise mechanism of FLOT2 in glioma is still limited. In this study, we demonstrated that FLOT2 expression levels were greatly upregulated in glioma tissues and cell lines, and the FLOT2 expression in glioma tissue was markedly associated with tumour stage and size. Overexpression of FLOT2 was correlated with poor prognosis of glioma patients. The functional assay revealed that silenced FLOT2 repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Previous studies found that miR-485 and miR-133 could target flotillin-2, resulting in inhibition of metastasis or epithelial-mesenchymal transition (EMT) in lung adenocarcinoma (18,19). Furthermore, flotillin-2 was targeted by miR-449 in glioma (20). In addition, miR-802 and miR-34a have also been reported to target flotillin-2 in prostate cancer and melanoma respectively (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that miR-485 and miR-133 could target flotillin-2, resulting in inhibition of metastasis or epithelial-mesenchymal transition (EMT) in lung adenocarcinoma (18,19). Furthermore, flotillin-2 was targeted by miR-449 in glioma (20). In addition, miR-802 and miR-34a have also been reported to target flotillin-2 in prostate cancer and melanoma respectively (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, certain aberrantly expressed miRNAs have been identified in glioma that serve crucial roles in tumor progression. For instance, downregulation of miR-449 was detected in glioma tissues and demonstrated to be involved in the tumor progression by targeting flotillin 2, which was associated with poor prognosis in patients with glioma (10). Upregulation of miR-6807-3p was observed in glioma specimens; miR-6807-3p promoted tumor progression and suppressed apoptosis by targeting dachshund family transcription factor 1 (11).…”
Section: Introductionmentioning
confidence: 99%
“…It is well acknowledged that miRNAs play pivotal roles in the physiological and pathological processes of multiple cancers, such as hepatocellular carcinoma, nasopharyngeal carcinoma, glioma, and GC [ 26 , 27 , 28 ]. As an oncogene or tumor suppressor, miRNA is involved in tumorigenesis by gene expression modulation at the posttranscriptional level [ 29 , 30 , 31 ]. Recently, the aberrant expression of miR-299-3p was identified to be associated with malignant clinicopathological characteristics and poor prognosis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%